Two Moments of the Spectator in the Work of Antonio Manuel - Hipólito, Rodrigo (Revista do Colóquio, 2021)
This text examines the position of the spectator through two works by Antonio Manuel, "Urnas-quentes" (1969) and "O Corpo é A Obra" (1970). Understanding these as two opposing cases, it demonstrates the active participation of the audience in the first case and passive participation in the second. This reasoning is guided by the context of conceptual openness and the insertion of the spectator, characteristic of the art produced in Brazil in the 1960s, to which the writings and statements of artists like Hélio Oiticica and Antonio Manuel himself, as well as close critics like Frederico Morais, give us access. The two works highlighted here are analyzed with the use of the audience as a point of reference and exemplify the problematic nature of the critical reception of works of art.